Investigating the Post-Sintering Thermal and Mechanical Treatments on the Properties of Alumina Reinforced Aluminum Nanocomposites - Tayyab Subhani; Abdulaziz S. Alghamdi; Abdul Khaliq; Adnan Munir; Muhammad Javaid Iqbal (Tehnički Vjesnik, 2023)
Alumina nanoparticles in the loading fraction of 3 wt% were incorporated in pure aluminum matrix to prepare nanocomposites for improved mechanical performance. Powder metallurgy route was adopted wherein nanoparticles were mixed with aluminium powder using dry mixing technique involving milling process, which was followed by the densification of composite mixture by uniaxial cold pressing and pressureless sintering. In order to increase the densification of nanocomposites, a batch of sintered nanocomposites was twice sintered at the same sintering parameters while another batch of specimens was cold pressed after initial sintering. The consolidated nanocomposites together with reference pure aluminum specimens were characterized microstructurally and mechanically by optical and electron microscopy, hardness and compressive strength tests. It was found that the hardness and compressive strength of nanocomposites after sintering increased up to ~ 29% and ~ 144% in comparison to pure aluminium specimens, respectively. Although the densification of nanocomposites increased after twice sintering, the hardness and compressive strength values decreased. However, the rise in consolidification along with improved mechanical performance was noted after cold pressing the specimens as secondary treatment after sintering; hardness increased up to ~ 36% while compressive strength rose to ~ 64%. In comparison to twice sintering, cold pressing after initial sintering significantly increased the hardness and compressive strength of nanocomposites up to ~ 76% and ~ 301% with reference to pure aluminum, respectively. It was found that both the incorporation of alumina nanoparticles and cold pressing after initial sintering improved the mechanical properties of nanocomposites.